(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the impact of exchange rate movements on India’s import and export sectors. Using secondary data from RBI (Reserve Bank of India), EXIM (Export Import) Bank, government reports and research journals, this study finds out that Rupee depreciation improve export-oriented sectors like IT, textiles and agricultural sectors by making Indian products and services competitive in global market. However, import-dependent industries like petroleum, electronics, gems and jewellery face increasing costs, inflation, and higher debt burdens. This research highlight the role of factors like inflation, interest rates and geopolitical tensions in exchange rate fluctuations. This study recommends hedging strategies, domestic substitutes, MSME support and Rupee internationalization to reduce dependency of international currency like Dollar.